Optimum gas turbine configuration for improving the performance of combined cycle power plant - Ibrahim, Thamir K.; M. M., Rahman; Abdalla, Ahmed N. (Elsevier Ltd, 2011)
The thermodynamic analysis of combined cycle gas turbine with effect different configuration for gas turbine are presented and discussed in this paper. The effects of ambient temperature and compression ratio have been proposed to select optimum configuration for gas turbine and its effect on CCGT performance. The analysis performance code has been performed used the MATLAB software. The simulating code for gas turbine configuration results show that the simple gas turbine configuration is more suitable with regards to power output, but the regenerative gas turbine configuration has higher efficiency with effect ambient temperature. The simple gas turbine configuration has higher power output with effect the compression ratio, while the regenerative gas turbine configuration has higher efficiency with effect lower compression ratio, therefore the variation of total power output is insignificance at lower compression ratio. The extensive modelling performed in this study reveals that, the ambient temperature and compression ratios are strongly influence on the performance of combined cycle, a higher overall efficiency can be achieved for combined cycle with add regenerative to topping cycle.